Skills for the future: an instructional systems design approach to youth development programming - Gough, Michelle Lee (My University, 2025)
Integrating social-emotional learning, digital literacy, and employability skills into an intentionally designed Positive Youth Development (PYD) program equips students with the competencies needed for skills-based hiring, expanding opportunities for hidden talent pools, promoting workforce diversity, and fostering economic growth. This study employed a qualitative conceptual content analysis of three competency frameworks, social-emotional learning, digital literacy, and employability skills, to identify overarching competencies shared across the frameworks. The analysis revealed six key competencies: self-management and adaptability, effective communication and collaboration, critical thinking and problem-solving, technical and digital literacy, ethical and cultural awareness, and lifelong learning and professional development. These competencies were evaluated against PYD principles using a rubric, ensuring alignment with core PYD goals such as viewing youth as resourceful assets, fostering agency, engaging them as community contributors, and creating environments that support skill-building. The conceptual Young Curators program was developed using the findings and the Instructional Systems Design (ISD) process to integrate these competencies into a structured, intentional, and holistic framework. The program aligns theoretical frameworks with practical applications, promoting scalability, equity, and measurable outcomes. This approach effectively prepares youth for diverse challenges, supporting PYD's mission to empower young people to be healthy, productive, and engaged members of their communities.
Keywords: Instructional design; Youth development programs